2010
DOI: 10.1515/jpm.2009.123
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid volume in intra-amniotic inflammation with and without culture-proven amniotic fluid infection in preterm premature rupture of membranes

Abstract: Objective: Previous studies reported that the clinical significance of intra-amniotic inflammation with a negative amniotic fluid (AF) culture is similar to that of intra-amniotic inflammation with microbiologically-proven AF infection. However, the magnitude of the fetal inflammatory response in these two conditions is different as gauged by umbilical cord C-reactive protein (CRP) concentrations. We undertook this study to determine if the frequency of oligohydramnios is different in these two conditions. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
1
27
1
2
Order By: Relevance
“…Previous studies have shown that FIRS in PPROM is associated with significant oligohydramnios at admission, and therefore, presumably, with reduced renal blood flow as the underlying pathophysiologic mechanism [28] . Additional possible explanations of the link between oligohydramnios and FIRS include the reduced antimicrobial properties of amniotic fluid and/or redistribution of blood flow away from the kidneys, inducing oligohydramnios [29] .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that FIRS in PPROM is associated with significant oligohydramnios at admission, and therefore, presumably, with reduced renal blood flow as the underlying pathophysiologic mechanism [28] . Additional possible explanations of the link between oligohydramnios and FIRS include the reduced antimicrobial properties of amniotic fluid and/or redistribution of blood flow away from the kidneys, inducing oligohydramnios [29] .…”
Section: Discussionmentioning
confidence: 96%
“…The AF IL-6 concentrations were used to assess the presence and magnitude of an inflammatory response based upon previous studies conducted by us and others [7881,85, 90, 96, 163172], which indicate that AF IL-6 concentrations correlate with the outcome of preterm labor [11,63, 79, 88, 173179], preterm PROM [173, 180, 181], cervical insufficiency [182], placenta previa [89], and a short cervix [183186]. The median AF IL-6 concentration in patients with clinical chorioamnionitis and microbial-associated intra-amniotic inflammation was 14 ng/mL, which was higher than that of patients with intra-amniotic inflammation without detectable microorganisms (4.7 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that intrauterine infection is an important mechanism leading to preterm labor and may account for 40% of preterm births (68). However, this number may be higher because many infections are likely to be subclinical and the pathogenesis is not detected due to the lack of sensitivity of conventional culture techniques(9) (10).…”
Section: Introductionmentioning
confidence: 99%